2021
DOI: 10.1093/trstmh/trab129
|View full text |Cite
|
Sign up to set email alerts
|

The coverage of hepatitis B birth dose vaccination in Nigeria: Does the place of delivery matter?

Abstract: Background Hepatitis B birth dose (HepB-BD) vaccination coverage remains suboptimal in Nigeria. While evidence suggests that institutional delivery is associated with the uptake of HepB-BD vaccine, little is known about how the uptake differs by facility ownership (public or private). This study examined the HepB-BD vaccination coverage by place of delivery in Nigeria. Methods This study is a secondary analysis of data on 614… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The latter are better off in terms of health infrastructure and human resources in health [23] . In Nigeria, a similar result was found [34] . Overall, this study highlights the existence of inequity in timely vaccination because coverage varies significantly in terms of social and geographic characteristics.…”
Section: Determinantssupporting
confidence: 76%
“…The latter are better off in terms of health infrastructure and human resources in health [23] . In Nigeria, a similar result was found [34] . Overall, this study highlights the existence of inequity in timely vaccination because coverage varies significantly in terms of social and geographic characteristics.…”
Section: Determinantssupporting
confidence: 76%
“…Several studies have investigated the programmatic barriers to optimal uptake of the hepatitis B birth-dose vaccine in Africa, using both quantitative and qualitative research approaches. Some of the barriers reported across the literature include the lack of relevant policies at both national and health-facility levels [73,74], lack of funding or out-of-pocket payment requirements [75], poor monitoring and evaluation systems [73,74], lack of integration with the maternal and child health package [14,74], lack of awareness about HBV infection and hepatitis B birth-dose vaccination among pregnant women [75,76], geographical inaccessibility of immunization clinics [75,77], inaccessibility due to allotted vaccination days [74,75], frequent stockouts [75,78], home births [79,80], lack of outreach services [74], mistrust of HCWs handling newborns [76], birth doses administered on discharge only [74], poor knowledge of contraindications among HCWs, and absence of delineated staff [74]. In 2017, Breakwell et al published a MEDLINE literature review citing (i) timely administration, (ii) the high prevalence of home births, (iii) the lack of services available to reach infants born at home, and (iv) unreliable vaccine supplies as challenges limiting improved adoption and coverage of the hepatitis B birth-dose vaccination program [2].…”
Section: Challenges Faced By Established Hepatitis B Birth-dose Vacci...mentioning
confidence: 99%
“…Of the four, only one publication described programmatic barriers, which suggested that living in rural areas was the most weighted risk factor limiting access to the hepatitis B birth-dose vaccine post-delivery [48,77]. despite integration with the national immunization schedule [80,82]. While calls for improved institutional delivery are valid [1,2,81], it remains important that national health systems become more responsive to cultural contexts where home births and isolation periods post-birth are concerned [2,76,77].…”
Section: Challenges Faced By Established Hepatitis B Birth-dose Vacci...mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, high cost of diagnostic testing and out of pocket expenses for viral hepatitis treatment, low capacity of health care providers, and the proliferation of sub-standard treatment centers across Nigeria constitute a challenge to the elimination goal of hepatitis in the country [14]. All these factors could account for poor birth-dose HBV vaccination in Nigeria, which has a 51-53% coverage rate [15,16].…”
Section: Introductionmentioning
confidence: 99%